Benægtelse af Holocaust - historieforfalskning lever på nettet - Molbæk-Steensig, Sine (Rambam. Tidsskrift for jødisk kultur og forskning, 2013)
Holocaust Denial - Falsification of History is Alive on the World Wide Web Although the Holocaust is the most documented genocide ever, there are people who deny that the murder of the European Jews took place. According to the deniers, the Holocaust is a myth sustained by pro-Jewish historians, journalists, politicians, teachers, and NGOs. The deniers argue that the Holocaust was invented to blackmail Germany for money after the war and to justify the establishment of Israel in the Middle East and, moreover, the Holocaust ensures that no one dares to criticise Jewish influence in the world – especially culturally and economically. The denial of the Holocaust takes several forms and is done for several reasons, but there is always an element of anti-Semitism involved; the deniers take departure in the already existing anti-Semitic stereotypes and prejudices which they reproduce in a more or less direct way, especially the idea of a worldwide Jewish conspiracy. Twenty years ago, very few had ever heard of the deniers and now the phenomenon is commonly known because the internet has made it possible for deniers to spread their message to every conceivable corner of the world. But the technology, on the other hand, has also made it possible for a larger audience to find valuable knowledge about the Holocaust.